2019
DOI: 10.31682/ayna.482168
|View full text |Cite
|
Sign up to set email alerts
|

Lacanian Discourse Analysis Perspective in Psychology: Investigating the Relationship between Substance Addiction and Law in a Therapy Process

Abstract: Günümüzde bağımlılık oranlarında ve türlerinde yüksek oranda artış görülmektedir. Bu artışla eş zamanlı olarak bağımlılığın önlenmesine yönelik kurumsal ve yasal birçok düzenleme ortaya çıkmıştır. Ancak diğer yandan toplumsal söylemde, Özne'nin keyif verici maddelere ulaşmayı hak ettiğine dair birçok ifade ortaya çıkmaktadır. Bu çalışmada, madde bağımlılığı ile yasa ilişkisinin bir terapi sürecinde tarihi, kültürel ve güncel değerlendirmeler ışığında söylemsel temelde incelenmesi amaçlanmıştır. Bu amaçla, madd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…By employing these key elements, researchers using the LDA perspective aim to gain insights into how language constructs reality, how meaning is created, and how power and authority operate within the discourse. Research examples that adopt this methodology can be examined for further information (Baltacı & Gençöz, 2019; Brock, 2016; Dempsey, 2021; Frosh et al, 2003; Hook, 2013; Koren, 2014; Malone & Barabino, 2009; Roberts & Malone, 2014; Stavrakakis, 2014; Swales et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing these key elements, researchers using the LDA perspective aim to gain insights into how language constructs reality, how meaning is created, and how power and authority operate within the discourse. Research examples that adopt this methodology can be examined for further information (Baltacı & Gençöz, 2019; Brock, 2016; Dempsey, 2021; Frosh et al, 2003; Hook, 2013; Koren, 2014; Malone & Barabino, 2009; Roberts & Malone, 2014; Stavrakakis, 2014; Swales et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Parker (2005b) defines discourse as a powerful image of the self and the world and suggests that discourse demonstrates how the language is organized by the speaker themselves (Pavón-Cuéllar & Parker, 2014). He criticizes the traditional discourse analysis approach of Potter and Wetherell for its singular focus on diversity, arguing that it should instead concentrate on contradictions (Baltacı & Gençöz, 2019). According to Parker, discourse analysis should pay particular attention to the text's self-opposition, issues of power, and sociohistorical construction.…”
Section: The Perspective Of Lacanian Discourse Analysismentioning
confidence: 99%
“…Araştırmadaki etkisinin ve konuyla nasıl ilişkilendiğinin farkında olan araştırmacı, araştırma konusuyla ilgili daha geniş bir bakış açısına sahip olur. Bu anlamda araştırmacının sadece araştırma konusuna olan yatırımı ve araştırma konusu doğrultusundaki ilgisi değil teorik ve kurumdaki pozisyonlanışı da önem taşımaktadır (Baltacı ve Gençöz, 2019). Araştırmada yapılan seçimlerin teorik, kuramsal ve metodolojik duruşla alakalı olduğu kadar araştırmacının sosyal, toplumsal ve politik duruşuyla da ilişkili olduğu yadsınamaz (Mauthner ve Doucet, 2003).…”
Section: Refleksiviteunclassified
“…Bu ilişkiyi inceleyen nitel çalışma ise çok azdır. Baltacı ve Gençöz (2019), madde bağımlılığı ve yasa ilişkisini terapi sürecinde Lacanyen Söylem Analizi ile inceleyen nitel bir araştırma yapmışlardır. Bir vaka incelemesi olan bu çalışma, hastanın terapilerde madde kullanımının yasak olduğunu bilmesine rağmen terapistte bu konuda şüphe uyandırdığını ortaya koymuştur.…”
Section: Introductionunclassified
“…Quantitative studies have revealed that addiction is related to legal problems and rule violations (Altuner et al, 2009;Darke et al, 2010;Oroszi, 2019). A qualitative study examining the relationship between drug addiction and the law revealed that addiction is associated with an attempt to suspend boundaries (Baltacı & Gençöz, 2019). However, more qualitative studies are needed to further explore the relationship between addiction and law, rules, and boundaries.…”
Section: Introductionmentioning
confidence: 99%